The Impact of Electronic Publication on Contact List Performance in Electronic Journalism - sabi, fatima (Journal of Social Sciences and Humanities, 2020)
Media has witnessed rapidly development in its technique production, by adopting technological means and using them. All media follow the electronic mode in order to improve their performance, this later affect on the contact list s performance through the use of multimedia and supporting their contents by graphs .The electronic publishing also facilitates the production of the media content level starting by; getting the source of the information and collecting them, then using the electronic means and store them electronically. In light of the developments resulting from the applications of the Internet in the field of media and journalism, which resulted in the emergence and spread of the so-called electronic press, which is characterized by instantaneous and immediate continuous live news as it happens from anywhere in the world, without any barriers to the arrival of those messages and In the midst of these transformations that the electronic journalism production has witnessed, the news was further reflected on the gatekeeper s role and the nature of the tasks entrusted to him in the new environment . New technologies have transformed the field of media work in general and the field of journalism in particular and the ways in which it is practiced. This is evident in the creation of mobile devices (smartphones and smart tablets) and the development of their applications with multiple possibilities. Media institutions, they began to use. This has led to the emergence of mobile journalism, which is rapidly gaining popularity among professional and amateur media professionals because of its positive reflection and fundamental changes that touched the ways of practicing journalism.